Investigation of anti-cardiac hypertrophy effects of Andrographis paniculata ethanolic extract by modulating proinflammation and oxidative stress via Nrf2/NF-kB/NLRP3 signaling pathway: In silico and in vitro approaches - Muhamad Rizqy Fadhillah, Heri Wibowo, Arleni Bustami, Dewi Sukmawati, Aryo Tedjo, Nurul Gusti Khatimah, Ippei Shimizu, Wawaimuli Arozal (Journal of Applied Pharmaceutical Science, 2025)
Previous studies showed that Andrographis paniculata exhibits antioxidant and anti-inflammatory properties, possibly by modulating the nuclear factor erythroid 2-related factor (Nrf2)/nuclear factor-kappa B (NF-κB)/NLR family pyrin domain-containing 3 (NLRP3) pathways. However, no research has investigated its potential for preventing cardiac hypertrophy through this pathway. This study aims to investigate the main compounds of A. paniculata ethanolic extract (APE) and decipher its potential effect against anti-cardiac hypertrophy by modulating Nrf2/NF-?B/NLRP3 pathways, using both in vitro and in silico approaches. APE metabolites were analyzed through qualitative reagent-based phytochemical testing and quantitative gas-chromatography mass-spectrometry (GC-MS) analysis. APE’s anti-hypertrophic activity was evaluated in Ang-II-treated H9c2 cells. Cell-size area and hypertrophic gene expression were measured alongside proinflammatory mRNA expression (NF-κB, NLRP3, and IL-1β) and antioxidant mRNA expression (Nrf2, SOD1) with the levels of superoxide anion and hydrogen peroxide. The abundant compounds were analyzed using an in silico approach by docking, fingerprint analysis, and pharmacokinetic prediction. GC-MS showed that gamma-sitosterol, Andrographolide, Cortolone, stigmasterol, and 2,6,10,15,19,23-Pentamethyl-2,6,18,22- tetracosatetraen-10,15-diol were the most abundant in APE. In vitro studies showed APE suppresses Ang-II-treated H9c2 cell hypertrophy and limits the proinflammation and oxidative stress process through Nrf2/NF-?b/NLRP3 signaling. In silico studies revealed these compounds have low binding energy to Inhibitor of Kappa, Kelch-like ECH-associated protein 1, and NLRP3 proteins. They also exhibited good predicted IC50 values, favorable ligand efficiency lipophilicity values, and a desirable pharmacokinetic profile. This in vitro study exhibited that APE inhibits the Ang- II-treated H9c2 hypertrophy by modulating proinflammation and oxidative stress through the Nrf2/Nf-κB/NLRP3 pathway, thereby reducing proinflammation and oxidative stress. In silico analysis found that the entire abundant compound exhibited good molecular interaction, with Andrographolide and Cortolone are potential drug candidates that need further investigation.
Keywords: Cardiac hypertrophy, Andrographis paniculata, Nrf2/NLRP3/NF-?B signaling pathway, H9c2, in silico screening